PID Controller For Six Degrees Of Freedom (DOF) Stewart Platform Hexapod - Sobri, Mohamad Hafiz (2017)
This project is about the study of controlling the stability of Stewart platform which can perform six degrees of freedom (DOF) through the axes of x,y and z. In the current industries, Stewart Platform is used as flight simulators and automatic robot surgery but in this project’s scope, it is used as a tool for auto adjustment of a camera platform. Stewart platform consists of two platforms, base and top platforms in which the top one is the one that moves and the bottom one will remain static. The movement of the top platform is affected by the upright and downright motion of its six actuator legs. Stewart platform needs to be enhanced to ensure the stability of the load on top of it. PID control technique is needed for the purposes with the help of sensors to achieve the desired outcome. The results from the simulation and experimental show that the objectives can be achieved but are restricted to some limitations. The outcomes of this project prove that PID control method is effective in controlling the stability of the top platform of Stewart platform.